1977
DOI: 10.1007/bf01654719
|View full text |Cite
|
Sign up to set email alerts
|

Review of elective surgical treatment of chronic duodenal ulcer

Abstract: This article is a review of 20 clinical trials of various forms of elective surgical treatment of chronic duodenal ulcer conducted between 1964 and 1975, some of them prospective and others retrospective in nature. Comparisons have been made of the results following truncal vagotomy with drainage, truncal vagotomy with antrectomy, and partial gastrectomy. Additionally, selective vagotomy and truncal vagotomy have been compared in some studies and various forms of drainage, such as pyloroplasty and gastrojejuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…This is comparable with other reports in the literature [22][23][24][25] and indicates a satisfactory operative procedure. The morbidity of vagotomy and drainage or gastrectomy with particular reference to vomiting, diarrhea, dumping, and weight loss has been documented by our unit [26] and others [27][28][29][30]. These complications, when severe, frequently do not respond to treatment [14,20,25,31,32].…”
Section: Discussionmentioning
confidence: 88%
“…This is comparable with other reports in the literature [22][23][24][25] and indicates a satisfactory operative procedure. The morbidity of vagotomy and drainage or gastrectomy with particular reference to vomiting, diarrhea, dumping, and weight loss has been documented by our unit [26] and others [27][28][29][30]. These complications, when severe, frequently do not respond to treatment [14,20,25,31,32].…”
Section: Discussionmentioning
confidence: 88%
“…We found in the medical literature 1 report of just 5 cases of gastric pseudotumor by CMV, of which, only 3 cases were reported causing stenosis by the lesion [ 10 ]. Kelesidis et al described a case of duodenal pseudotumor solved by oral treatment with valganciclovir and reported another 14 cases of CMV pseudotumor in other parts of the gastrointestinal tract in their patients [ 20 ]. They cautiously concluded that this successful treatment with complete resolution of CMV’s pseudotumor in their HIV immunosuppressed patient with medication was a unique case in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment for duodenal stenosis, which can be caused by malignancy, peptic ulcer, or other specific agents, may involve procedures with surgical resection like partial gastrectomy or bypass techniques like pyloroplasty. Bypass surgery can be done by several approaches as described by Heineke-Mikulicz, Finney, Jaboulay, Finsterer-Bancroft, as well as gastroenteroanastomosis [ 17 – 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, in accordance with a previous report [2], selective proximal vagotomy was performed to reduce postoperative gastric acid secretion. Next, for prevention of gastroesophageal reflux, Toupet fundoplication was carried out.…”
Section: Case Reportmentioning
confidence: 90%
“…Perforations related to peptic ulcer disease are most common among benign disorders, while carcinoma is the most prevalent malignant condition. Overall, duodenal or gastric ulcer is the most frequent cause of perforation [1,2]. Accompanying symptoms usually include epigastric pain, abdominal distention, and fever that are suggestive of acute abdomen, a condition requiring emergent surgical intervention.…”
Section: Introductionmentioning
confidence: 99%